(untitled) (Bangladesh Medical Journal, 2016)
Globally, occupational risks have been classed as the tenth leading cause of morbidity and mortality and occupational skin diseases are important problem in the construction industries. The current study was conducted to see the prevalence and pattern of skin diseases among construction workers in Dhaka city. This cross sectional observational study was conducted in the Department of Dermatology and Venereology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, Bangladesh from July 2013 to June 2014. Four hundred workers were randomly enrolled from 20 construction areas of Dhaka city. History were taken, physical examination and laboratory tests were done to see the presence and pattern of skin diseases. Among 400 workers only 23.0% uses protective measure and 59.5% has been suffered with at least one form of skin disease. Among them different dermatoses were found in following percentages i.e. irritant contact dermatitis (ICD) (28.15%), allergic contact dermatitis (ACD) (9.24 %), acne (14.29%), seborrheic dermatitis (10.92%), burn/scald (5.46%), accidental injury (7.14%), scabies (23.53%), fungal infection (dermatophytosis/pityriasis versicolor/candidiasis) (23.53%), palmoplantar keratoderma (13.87%), lichen simplex chronicus (3.78%), pyoderma (4.20%) and urticaria (2.52 %). Construction workers in Dhaka city bear a great burden of skin diseases, among which contact dermatitis is the most common and other skin diseases include fungal infection, scabies and acne. These occupational skin diseases may be prevented by providing improved work place, protective means, health education, adequate health services and improving professional skills. Bangladesh Med J. 2015 Jan; 44 (1): 11-15